1999
DOI: 10.1051/rnd:19990501
|View full text |Cite
|
Sign up to set email alerts
|

Can embryo metabolism be used for selecting bovine embryos before transfer?

Abstract: -The quality of in vitro-produced bovine embryos remains variable.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…As 3-aminoisobutyrate can be derived from the TCA cycle intermediate succinyl-CoA, this may also be indicative of a decrease in TCA cycle metabolism. Previous studies have found a significant net appearance of alanine in the media of developing embryos [Houghton et al 2002] and it has been proposed that alanine provides a means of disposing of ammonia via the enzymes glutamate dehydrogenase and alanine transaminase [Donnay et al 1999]. A decrease in the levels of alanine in media has previously been associated with development to the blastocyst stage compared to those embryos that arrested [Houghton et al 2002].…”
Section: Discussionmentioning
confidence: 99%
“…As 3-aminoisobutyrate can be derived from the TCA cycle intermediate succinyl-CoA, this may also be indicative of a decrease in TCA cycle metabolism. Previous studies have found a significant net appearance of alanine in the media of developing embryos [Houghton et al 2002] and it has been proposed that alanine provides a means of disposing of ammonia via the enzymes glutamate dehydrogenase and alanine transaminase [Donnay et al 1999]. A decrease in the levels of alanine in media has previously been associated with development to the blastocyst stage compared to those embryos that arrested [Houghton et al 2002].…”
Section: Discussionmentioning
confidence: 99%
“…Embryos become more dependent on aerobic metabolism and probably acquire a greater capacity to use glucose as the blastocyst forms (48)(49)(50) *Significantly different from anticipated 1:1 ratio of males to females (P Ͻ 0.05). † Significantly different from anticipated 1:1 ratio of males to females (P Ͻ 0.01).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in other species, including human and mouse, embryos compensate for the absence of glucose by increasing pyruvate consumption or maintaining it at a high level (Gardner & Leese, 1988;Conaghan et al, 1993). However, pyruvate plays also other important roles in embryo culture (Donnay et al, 1999) that could mask such effects in our study.…”
Section: Discussionmentioning
confidence: 77%
“…The spent culture drops were frozen at -80 °C in the culture dishes. Pyruvate, glucose and lactate concentrations were evaluated microfluorimetrically (Leese & Barton, 1984;Donnay et al, 1999). Pyruvate and glucose uptakes and lactate release by the embryos were evaluated by comparing the concentrations of substrates in spent medium with those of control drops.…”
Section: Experiments 3: Pyruvate and Glucose Uptake And Lactate Releasementioning
confidence: 99%